Improving students’ motivation through the use of interactive media in physical education learning - Al Hafiz Saputra; Rasyono; Weni Agustina (Sriwijaya Journal of Sport, 2025)
Research Problems: Students’ motivation in Physical Education learning is often low due to monotonous and less engaging teaching methods. The use of interactive media is expected to enhance students’ engagement and enthusiasm by providing a more interesting and enjoyable learning experience. Research Objectives: This study aims to improve students' learning motivation in PJOK subjects in class IX.1 SMPN 50 Palembang through the application of interactive learning media. The background of this study arose from the problem of low student learning motivation, especially in the PE theory material which is often considered monotonous and uninteresting. Methods: The Classroom Action Research (CAR) approach was used with the Kemmis and McTaggart model, which was implemented in two cycles. The interactive media used included digital presentations, learning videos, interactive quizzes, and simple visual exercises. Data were collected through observation, motivation questionnaires, interviews, and documentation. Results: The results of the study showed a significant increase in learning motivation, with the average questionnaire score increasing from 68 in the first cycle (moderate category) to 82 in the second cycle (high category). Improvements were also seen in active participation, enthusiasm for learning, and students' self-confidence during learning activities. Teachers stated that the use of interactive media made the learning process more effective, interesting, and easy to understand. Conclusion: Therefore, it can be concluded that interactive media plays a positive role in encouraging students' learning motivation in PJOK learning, and it is suggested that this strategy be applied more widely to various subjects to create a fun and meaningful learning atmosphere.